2016
DOI: 10.1002/cphc.201600343
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Ab Initio Investigation of C−H⋅⋅⋅N Hydrogen‐Bonded Complexes of Fluorophenylacetylenes: Frequency Shifts and Correlations

Abstract: The C-H⋅⋅⋅N hydrogen-bonded complexes of several fluorophenyacetylenes with ammonia and methylamine were characterized by a redshift in the acetylenic C-H stretching vibration of the phenylacetylene moiety. These redshifts were linearly correlated with the stabilization energies calculated at the CCSD(T)/CBS//MP2-aug-cc-pVDZ level. Analysis of various components of the interaction energy indicated that the observed redshifts were weakly correlated with the electrostatic component. The weaker linear correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Moreover, it was also shown that the dispersion energy component modulates the trends observed in total stabilization energy . On the other hand, for a series of ammonia and methylamine complexes of fluorine-substituted phenylacetylenes (PA), the shifts in the acetylenic C–H stretching vibration were linearly correlated with the stabilization energies . For a series of O–H···O hydrogen-bonded water complexes of fluorophenols, based on the correlation between the shifts in the O–H stretching frequencies and the stabilization energies, the complexes were categorized into two sets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was also shown that the dispersion energy component modulates the trends observed in total stabilization energy . On the other hand, for a series of ammonia and methylamine complexes of fluorine-substituted phenylacetylenes (PA), the shifts in the acetylenic C–H stretching vibration were linearly correlated with the stabilization energies . For a series of O–H···O hydrogen-bonded water complexes of fluorophenols, based on the correlation between the shifts in the O–H stretching frequencies and the stabilization energies, the complexes were categorized into two sets.…”
Section: Introductionmentioning
confidence: 99%
“…35 On the other hand, for a series of ammonia and methylamine complexes of fluorine-substituted phenylacetylenes (PA), the shifts in the acetylenic C−H stretching vibration were linearly correlated with the stabilization energies. 36 For a series of O−H•••O hydrogen-bonded water complexes of fluorophenols, based on the correlation between the shifts in the O−H stretching frequencies and the stabilization energies, the complexes were categorized into two sets. However, the energy decomposition analysis (EDA) revealed that the shifts in the O−H stretching frequencies were linearly correlated with the electrostatic component of the stabilization energy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There have been many works on the issue of two types of frequency shifts reporting a large number of correlations of various quantities with the objective of rationalising or predicting whether there will be red or blue shift. However, the issue is still not resolved and there are many attempts to provide further insight through several calculations [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and experimental investigations. [24][25][26][27][28] There is thus no single model or explanation that can definitely point out whether a hydrogen bond will show blue shift or red shift in its stable configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The IR spectra in the acetylenic CÀ H stretching region of all the MA complexes were recorded using the IR-UV double resonance spectroscopic method and are presented in Figure S1 (see the Supporting Information, SI). [9,12] Further, IR-UV hole-burning spectra were recorded, whenever required, to sort out multiple bands observed in Figure 1. The structures of the MA complexes were assigned based on the observed IR spectra with aid of highlevel ab-initio calculations at MP2/aug-cc-pVDZ//CCSD(T)/CBS level of theory and Figure 2 shows the structures of all the MA complexes responsible for spectra presented in Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%